Menuju Pelayanan Administrasi Kependudukan yang Terintegrasi Pada Implementasi Klampid New Generation (KNG) di Dinas Kependudukan dan Pencatatan Sipil di Kota Surabaya - Adine Venita Rizki; Nabila Sahda Brahmasta (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Implementation of Klampid New Generation (KNG) as an innovation in population administration services in the city of Surabaya. KNG is an online website that facilitates the management of population documents online, such as ID cards, family cards, birth certificates, and others. Through the Internship and Independent Study Certificate (MSIB) program, researchers were directly involved as Population Administration Service Assistants at the Surabaya City Village Office. Observations and active participation were carried out to collect primary data from village officials and the community. The research results show that although KNG is intended to facilitate independent document management, many residents still prefer to use village office services. This is due to a lack of socialization and public understanding about the use of KNG. In addition, there are also obstacles such as limited facilities and infrastructure in the village office that can hinder service performance. This research recommends the need for more intensive socialization and assistance to the community, as well as improving facilities at the village office to optimize the implementation of KNG in creating better population administration order in the city of Surabaya.